Faktor Kinerja Sistem Irigasi pada Tiga Daerah Irigasi di Kabupaten Dharmasraya - Muharma, Arma; Hasan, Alizar; Mizwar, Zuherna (Jurnal Talenta Sipil, 2024)
From the results of initial observations, it was found that the irrigation network management system in irrigation areas in Dharmasraya district was not managed properly and optimally, so that the impact was that many irrigation channels were found that were damaged and not well maintained. The purpose of this study was to identify the dominant factors and factors that influence the performance of the irrigation system in the three irrigation areas in Dharmasraya Regency, as well as to optimize the operation and maintenance of the network. This study used a quantitative method by distributing questionnaires to respondents. The results of the research conducted revealed 6 factors that influence the performance of the irrigation system in the three irrigation areas in Dharmasraya Regency, namely the P3A condition factor, the physical infrastructure condition factor, the planting productivity factor, the personnel organization factor, the facility factor. supporting, documentation factor